Czech and Slovak Democracy 20 years after and Theory of Modernisation - Valeš, Lukáš (Civilia, 2013)
The text deals with the application of modernization theory in the Czech-Slovak relations in the last twenty years that have elapsed since the division of the Czechoslovak state and in the broader historical context. Slovak modernization journey was shorter, more dynamic and successfully carried out in non-democratic regimes (fascism, communism). Significant native access both peoples is their relationship to the European Union and integration as the modernization significant momentum.
Keywords: Modernization; Czechs; Slovaks; Democracy